De‐epithelialized gingival graft versus subepithelial connective tissue graft in the treatment of multiple adjacent gingival recessions using the tunnel technique: 1‐year results of a randomized clinical trial. (7th April 2021) - Bakhishov, Hikmat; Isler, Sila Cagri; Bozyel, Bejna; Yıldırım, Benay; Tekindal, Mustafa Agah; Ozdemir, Burcu
Abstract: Aim: To compare the clinical efficacy and postoperative morbidity of de‐epithelialized gingival graft (DGG) with subepithelial connective tissue graft (SCTG) on treatment of multiple adjacent gingival recessions (MAGRs) with tunnel technique (TUN) and to evaluate histological characteristics of the palatal grafts. Materials and methods: Twenty‐seven patients with MAGRs affecting at least 2 adjacent teeth were treated with either DGG + TUN or SCTG + TUN. Recession depth(RD) and width(RW), probing depth(PD), clinical attachment level(CAL), keratinized tissue height(KTH), gingival thickness(GT), and complete and mean root coverage(CRC, MRC) were evaluated at 6 and 12 months postoperatively. Multilevel analysis was performed to identify patient‐ and tooth/site‐related predictors for the 12‐month MRC outcomes. Postoperative patient morbidity and histological characteristics of palatal graft samples obtained during harvesting were investigated. Results: At the 12‐month follow‐up, MRC was 91.72% ± 16.59% and 84.72% ± 19.72% in DGG + TUN and SCTG + TUN groups ( p  = .001). Multilevel regression analysis identified RD, KTH and GT as variables associated with MRC. No significant difference between the groups was observed regarding postoperative patient morbidity parameters. Cellularity was found significantly higher in the SCTG samples compared to the DGG samples ( p  < .05). Conclusions: Although DGG + TUN presented higher MRC and CRC compared to SCTG + TUN in the treatment of MAGRs, treatment method was not a significant predictive factor for the amount of MRC outcomes while RD, KTH and GT were significant predictive factors.